An Improved Simplified Rules Fuzzy Logic Speed Controller Method Applied For Induction Motor Drive - Talib, Md Hairul Nizam; Ibrahim, Zulkifilie; Rasin, Zulhani; Nordin, Nurdiana; Nabil Farah; Mohamad Razali, Azziddin; Abd. Rahim, Nasrudin (ISA - Instrumentation, Systems, and Automation Society, 2020)
Fuzzy Logic Speed Controller (FLSC) has been widely used for motor drive due to its robustness and its non-reliance to real plant parameters. However, it is computationally expensive to be implemented in real-time and prone to the fuzzy rules’ selection error which results in the failure of the drive's system. This paper proposes an improved simplified rules method for Fuzzy Logic Speed Controller (FLSC) based on the significant crisp output calculations to address these issues. A systematic procedure for the fuzzy rules reduction process is first described. Then, a comprehensive evaluation of the activated crisp output data is presented to determine the fuzzy dominant rules. Based on the proposed method, the number of rules was significantly reduced by 72%. The simplified FLSC rule is tested on the Induction Motor (IM) drives system in which the real-time implementation was carried out in the dSPACE DS1103 controller environment. The simulation and experimental results based on the proposed FLSC have proved the workability of the simplified rules without degrading the motor performance.